2015
DOI: 10.1002/cssc.201403287
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nitride in Energy Conversion and Storage: Recent Advances and Future Prospects

Abstract: With the explosive growth of energy consumption, the exploration of highly efficient energy conversion and storage devices becomes increasingly important. Fuel cells, supercapacitors, and lithium-ion batteries are among the most promising options. The innovation of these devices mainly resides in the development of high-performance electrode materials and catalysts. Graphitic carbon nitride (g-C3 N4 ), due to structural and chemical properties such as semiconductor optical properties, rich nitrogen content, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
108
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(108 citation statements)
references
References 156 publications
0
108
0
Order By: Relevance
“…Most of the recent studies found in the literature on g-C 3 N 4 refer to the photocatalytic hydrogen evolution promoted by this compound which confirmed that a polymeric g-C 3 N 4 photocatalyst is considered as a viable alternative to the actually known materials for hydrogen production under visible light irradiation (Cao et al 2015;Gong et al 2015;Ye et al 2015). Another interesting and very active area of investigation is the use of g-C 3 N 4 in the photocatalytic removal of test dyes, such as methyl orange (MO) (Han et al 2014;Tahir et al 2013;Yan et al 2009), rhodamine B (RhB) (Bu et al 2014;Chai et al 2014;Wang et al 2014), and methylene blue (MB) (Bai et al 2014;Li et al 2014;Zhu et al 2014).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Most of the recent studies found in the literature on g-C 3 N 4 refer to the photocatalytic hydrogen evolution promoted by this compound which confirmed that a polymeric g-C 3 N 4 photocatalyst is considered as a viable alternative to the actually known materials for hydrogen production under visible light irradiation (Cao et al 2015;Gong et al 2015;Ye et al 2015). Another interesting and very active area of investigation is the use of g-C 3 N 4 in the photocatalytic removal of test dyes, such as methyl orange (MO) (Han et al 2014;Tahir et al 2013;Yan et al 2009), rhodamine B (RhB) (Bu et al 2014;Chai et al 2014;Wang et al 2014), and methylene blue (MB) (Bai et al 2014;Li et al 2014;Zhu et al 2014).…”
Section: Introductionmentioning
confidence: 70%
“…+1.6 eV vs normal hydrogen electrode (NHE) ) which makes g-C 3 N 4 highly attractive for a range of reactions. In addition, it is stable up to high temperatures (up to 600°C in air), it can be easily prepared starting from cheap precursors, it is stable in several organic solvents, and it has a high resistance to chemical degradation both in acidic and alkaline environments (Cao et al 2015;Gong et al 2015;Ye et al 2015). Usually, g-C 3 N 4 is prepared by a simple thermal condensation of a nitrogen-rich precursor such as cyanamide ), dicyandiamide (Ji et al 2013), melamine (Yan et al 2009), thiourea (Zhang et al 2012), and urea (Dong et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, polymeric g-C 3 N 4 has become a focus of attention for photocatalytic reactions [14][15][16][17][18][19]. g-C 3 N 4 is a visible-light-response material ( 2.7 eV bandgap), and the energy position of CB and VB is at -1.1 and 1.6 eV vs normal hydrogen electrode (NHE), respectively [14].…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Opportunely, the natural structure of graphitic carbon nitride (g-C 3 N 4 ) contains large amount of pyrrolic N "hole" defect in the lattice and doubly bonded nitrogen at the edges of the vacancy, which are benefi cial for the adsorption and diffusion of lithium ion; [26][27][28][29] meanwhile, g-C 3 N 4 is inexpensive and nontoxic, and can be rapidly synthesized by the facile and scalable heating method, [ 30,31 ] avoiding the tedious pretreatment, multisteps, large quantities of toxic oxidants or reductants which are necessary for graphene preparation. On wileyonlinelibrary.com © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim the other hand, in order to adequately expose pyrrolic N "hole" defect of g-C 3 N 4 for lithium storage, it is suitable to immobilize nano particles into g-C 3 N 4 , where nanoparticles serve as spacers to isolate g-C 3 N 4 layers.…”
Section: Introductionmentioning
confidence: 99%